Examining the effects of creatine supplementation in augmenting adaptations to resistance training in patients with prostate cancer undergoing androgen deprivation therapy: a randomised, double-blind, placebo-controlled trial. Issue 9 (20th September 2019) - Fairman, Ciaran M; Kendall, Krissy L; Newton, Robert U; Hart, Nicolas H; Taaffe, Dennis R; Chee, Raphael; Tang, Colin I; Galvão, Daniel A
Abstract : Introduction: Creatine supplementation has consistently been demonstrated to augment adaptations in body composition, muscle strength and physical function in a variety of apparently healthy older adults and clinical populations. The effects of creatine supplementation and resistance training in individuals with cancer have yet to be investigated. This study aims to examine the effects of creatine supplementation in conjunction with resistance training on body composition, muscle strength and physical function in prostate cancer patients undergoing androgen deprivation therapy. Methods and analysis: This is a randomised, double-blind, placebo-controlled trial designed to examine the effects of creatine supplementation in addition to resistance training in patients with prostate cancer receiving androgen deprivation therapy. Both supplement and placebo groups will receive a 12-week supervised exercise programme comprising resistance training undertaken three times per week. The primary endpoint (fat-free mass) and secondary endpoints (fat mass, per cent body fat, physical fitness, quality of life and blood biomarkers) will be assessed at baseline and immediately following the intervention. Ethics and dissemination: The Human Research Ethics Committee of Edith Cowan University approved this study (ID: 22243 FAIRMAN). If the results of this trial demonstrate that creatine supplementation can augment beneficial adaptations of body composition, physical function and/or psychosocial outcomes to resistance training, this study will provide effect sizes that will inform the design of subsequent definitive randomised controlled trials. The results of this study will be published in peer-reviewed journals and presented at various national and international conferences. Trial registration number: ACTRN12619000099123